How the existence of special schools affects the placement of students with special needs in inclusive primary schools. Issue 3 (18th June 2022) - Ebenbeck, Nikola; Rieser, Jakob; Jungjohann, Jana; Gebhardt, Markus
Abstract : Although inclusion is the declared goal, the transition from a system based on special schools to an inclusive school system has only been progressing very slowly in individual countries. In an evolving school system, the existing special schools keep struggling to justify their existence. This study investigates the regional distribution effects based on official school data and shows the influence of a pull effect on special schools as a distance effect of special schools affecting the placement of students. For this purpose, official school statistics including all students at special and regular schools in the years 2010, 2015 and 2020 (N = 11 280 040) are evaluated in a spatiotemporal comparison using Educational Data Mining. In a hierarchical regression model on school placement in inclusive schools, the distance between primary and special schools has the highest influence ( β  = 0.48) on the inclusion rate (i.e., the proportion of students with special needs who are educated in regular schools in relation to all students with disabilities), along with the size ( β  = −0.14) and the density of special schools in a district ( β  = −0.12). The effects differ according to the population density of the region and are stronger in large cities. When the proportion of students with and without SEN in regular schools is considered (support rate), the density of special schools has the greatest impact on school placement ( ß  = 43.44). Self‐preservation of schools, traditional funding systems and regional differences between urban and rural areas are discussed as possible reasons.